Fuel price influence on the road users to ride public transport in UMS - Mohd Azizul Bin Ladin; Fariq Ismeth Jaimin; Syahira Diwa; Harryanshah Hamansa; Lim, Franklin, Tiam Yang (2018)
Fluctuation of fuel price (RM) per liter is one of the main factors that influences private vehicle users to shift to public transport.The main objectives of this study are to analyze the data related to the factors that influence the decision of students to use public transportation, and to develop a logistic model based on the shift percentage from private to public transportation influenced of fuel price (RM/Liter). This study is conducted in University Malaysia Sabah (UMS) and questionnaires was distributed to 377 of UMS students. Linear regression was used to analyze the collected data and develop a logistics model. From the model, the result shows that 87.53% of respondents are willing to shift to public transport should the fuel price reach RM3.50 per litre. This logistic model will be useful especially for the use of transportation planning in UMS.